Jackie Robinson: Changing the Game - Benjamin, Lisa (Zaner-Bloser, Inc.)
This book tells the biography of Jackie Robinson and how he is been celebrated by a museum in Washington D.C.
Keywords: Juvenile Non-Fiction / Biographies